Enhancing Critical Thinking in Junior High School through Project-Based Learning - Ningsih, Erlinda; Yusof, Khairunnisa M. (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This study investigates the efficacy of the Project-Based Learning (PjBL) model in enhancing critical thinking skills among junior high school students in Indonesia, addressing a documented deficit often linked to traditional, teacher-centered pedagogy. Employing a quasi-experimental, nonequivalent control group design, the study involved 60 eighth-grade students. The experimental group received a PjBL intervention focused on a real-world problem, while the control group followed a conventional lecture-based curriculum. Critical thinking skills—assessed through a validated pre-test and post-test measuring interpretation, analysis, inference, evaluation, and explanation—served as the primary dependent variable. An independent samples t-test revealed a statistically significant improvement (p<0.05) in the mean critical thinking scores for the PjBL group. In contrast, the control group exhibited negligible growth. The findings provide strong evidence that PjBL is a highly effective strategy for developing critical thinking. By engaging students in active, collaborative, and inquiry-driven processes, the model offers a practical solution to a persistent educational challenge, holding significant implications for curriculum reform and teacher development.